Preface - Argyros, Ioannis K; Magreñán, Á. Alberto (Iterative Methods and Their Dynamics with Applications: A Contemporary Study, 2020)
Capítulo del libro "Iterative Methods and Their Dynamics with Applications"
Keywords: computer science; mathematics & statistics; Scopus(2); WOS(2)